Organizational models in athletic training and the effect on the quality of care delivered - Ferreira, M. (College of Physical Activity and Sport Sciences at West Virginia University, 2019)
Context: Quality of care is an ethical priority to all healthcare professionals. Healthcare fields such as nursing and physical therapy have made changes in staff size and focus that have increased the quality of care provided to patients. The athletic training field has not made changes to the organizational structure. Thus, the quality of care delivered by athletic trainers is an understudied topic. Likewise, the organizational models have just recently been explored in the literature. Objective: Identify differences in the three models of organization (academic, athletic, and medical) related to quality of care delivered and coverage versus care. Design: This study was a prospective exploratory questionnaire analysis. Setting: Clinically practicing athletic trainers in the NCAA Division I setting of the United States. Patients and Other Participants: A randomized list of 1,000 National Athletic Trainers` Association (NATA) members who are Board of Certification (BOC) certified and clinically practicing in the NCAA Division I setting. The list was used to recruit participants to the questionnaire. Participants were required to be full-time, clinically practicing athletic trainers in the NCAA Division I setting. Participants were excluded if they are less than 18 years of age, not practicing in the Division I setting as an athletic trainer (AT), and are not employed full time (i.e. GAs, interns, residents). There were 66 valid responses recorded of the 1,000 potential participants (0.06% return rate). Intervention: Participants were contacted via the NATA Research Survey Service via e-mail. The e-mail contained a cover letter and link to a questionnaire. Two-weeks after the initial e-mail a followup letter with the link to the questionnaire was sent to encourage participation. The questionnaire contained 52-questions related to the perception of the quality of care delivered, whether the focus is on coverage or care, and demographic questions. Main Outcome Measures: Athletic trainers self-perception of the quality of healthcare they delivered and whether the focus is on coverage or care and the relationship to the model of organization (academic, athletic, medical) used. Results: 86.5% of participants were categorized into the athletics model of organization. There were 49 (74%) of participants in the high-quality care category. Seventy-seven percent of participants were in the high-coverage category. There was a significant relationship (p = .021) betwe the model of organization and the quality of care category. Conclusion: Athletic trainer self-perception of the quality of care delivered to patient is high. Athletic trainers in the medical model provided the highest quality care, but they are also still spending time in the work day providing coverage to practices and competitions. The athletics model, though not the ideal environment for quality healthcare, could foster quality if the staff, facilities, and team physicians make improving the quality a priority.